Non–commutative convolutional codes over the infinite dihedral group. (10th April 2015) - Candau, Marion; Gautier, Roland; Huisman, Johannes
Classic convolutional codes are defined as the convolution of a message and a transfer function over ℤ. In this paper, we study convolutional codes over the infinite dihedral group D∞ . The goal of this study is to design convolutional codes with good and interesting properties and intended to be more resistant to code recognition. Convolution of two functions on D∞ corresponds to the product of two polynomials in the non–commutative polynomial algebra 𝔽2 {X, Y}/{X² − 1, Y² − 1}. We show how encoding over D∞ can be represented by two classical convolutions over ℤ. Furthermore, we adapt the Viterbi algorithm to decode these codes using two different trellises. Finally, we show that these codes have performances similar to classic convolutional codes, but are not more resistant to code recognition. However, we get more optimal codes in terms of free distance than conventional.